177 Impact of Socioeconomics on Loss to Follow-up Following Emergent Surgery for Acute Subdural Hematoma. (1st April 2022) - Guidry, Bradley; Tang, Alan R.; Thomas, Harrison; Sermarini, Anthony; Dambrino, Robert J.; Yengo-Kahn, Aaron M.; Chambless, Lola B.; Morone, Peter J.; Chotai, Silky
Abstract : INTRODUCTION: Loss to follow-up (LTF) represents an obstacle in the post-surgical management of patients following acute subdural hematoma (aSDH) evacuation. Identifying the factors associated with LTF is required to improve patient care. We sought to examine potential factors with an emphasis on socioeconomic status (SES). METHODS: A retrospective analysis of patients treated surgically for aSDH from 2009-2019 at a level 1 regional trauma center was conducted. The primary outcome was LTF, defined as being scheduled but not receiving any follow-up care post-discharge. The main exposure was Area Deprivation Index (ADI), a neighborhood level composite of education, employment, housing quality, and poverty; this was used to measure SES with higher ADI corresponding to lower SES. Additional candidate factors were identified in the literature and through univariate comparisons of group characteristics. To reduce the number of variables, principal components analysis (PCA) was used; the first six principal components (PCs) contained 82% of the total variance. Multivariable logistic regression was performed to identify the PCs associated with LTF. RESULTS: Of the 172 patients included in the study, 36 patients were LTF (21%). The predominant PCs were as follows: increasing age, craniotomy instead of craniectomy, and decreased LOS in PC1; ADI and distance to hospital in PC2; unfavorable discharge mRS and non-home disposition in PC3; uninsured/Medicaid status and increased LOS in PC4; number of comorbidities in PC5; and transfer from OSH and use of craniectomy instead of craniotomy for PC6. In multivariable analysis for LTF, greater ADI and distance to hospital via PC2 (P = 0.009) and uninsured/Medicaid status and increased LOS via PC4 (P = 0.009) were associated with increased odds of LTF. CONCLUSION: Socioeconomic factors including increased neighborhood disadvantage, increased distance to hospital and uninsured/Medicaid status impact LTF following emergent surgery for aSDH. These patients with limited resources are at increased risk of losing continuity of care. The health care system must direct efforts to reduce healthcare disparity in these high-risk population.